Justice league the brave and the bold - Warner Home Video; Warner Home Video (Phils.). (Burbank, Calif. Warner Home Video ; distributed in the Philippines by Warner Home Video (Phils.), 2007)
The first showdown pairs Green lantern and The Flash against Gorilla Grodd, an evil genius primate with a mind-controlling device and a vendetta against humankind. Only the Justice League can save us from gorilla dominations! Then Lex Luthor's reputation as a devious mastermind is finally exposed...or is it? Luthor assembles a mighty evildoer team-Ultra-Humanite, Cheetah, Copperhead, Solomon Grundy, Star Sapphire, The Shade and The Joker-to destroy the Justice League. This is the one battle might and wits that could truly finish the Worlds Greatest Superhero.
Based on DC Comics characters.
Originally produced as an episode of the television program Justice League in 2002.
Episodes: The brave and the bold (Part 1) -- The brave and the bold (Part 2) -- Injustice for all (Part1) -- Injustice for all Part 2).
MPAA rating: Not rated.
VCD
Keywords: Justice League of America (Fictitious characters) -- Juvenile films; Heroes -- Juvenile films; Life on other planets -- Juvenile films